A Health Surveillance Study of Workers Employed at a Copper Smelter—Effects of Long-Term Exposure to Copper on Lung Function Using Spirometric Data. Issue 8 (1st August 2021) - Haase, Lisa-Marie; Birk, Thomas; Bachand, Annette M.; Mundt, Kenneth A.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Significantly lower permissible occupational exposure limits for copper dust are being discussed in Europe and other jurisdictions. However, little data are published on exposures in occupational settings and copper-specific effects in humans. Hence, a health surveillance study was performed among workers employed at a copper smelter between 1972 and 2018. Methods: Possible effects of long-term exposures to dust containing copper on lung function were assessed. Specifically, declines in forced expiratory volume in 1 second (FEV1 ) were compared between a copper-exposed and control group. Cumulative copper exposures were derived from historical airborne monitoring data. Results: FEV1 declines among exposed and control never smokers were similar to a typical age-dependent decline of 29 mL/y. Conclusion: The study findings indicate that cumulative inhalable copper dust exposure averaging 4.61 mg/m 3 -years over an exposure duration of ∼22 years is not associated with adverse effects on lung function.